PEMANFAATAN SANA KEBO DAN JARAK DALAM MATERI KARYA SENI TIGA DIMENSI DARI TANAH LIAT PADA SIMULASI PEMBELAJARAN INTERAKTIF SISWA KELAS INKLUSIF DI SLB NEGERI KOTA MAGELANG KELAS VI SDLB JURUSAN C - Kiftirul 'Aziz (Jendela Inovasi Daerah, 2020)
The purpose of using the sap of sana kebo and jarak is to improve the quality of three-dimensional artwork from clay materials of grade VI SDLB-C and SD students by understanding the following matters, namely: (1) introducing natural materials that are cheaper and safer for environment, (2) improving the quality of finishing three-dimensional artwork created by students, and (3) stimulating students' thinking patterns to better explore alternative materials that can be found in the natural surroundings. This best practice was carried out in class VI of Kedungsari 5 Elementary School, Magelang City and class VI SDLB-C, Magelang City. There are several variations of shapes that students can choose from, among others: (1) flora models, (2) fauna models, (3) geometric models, and (4) figurative models. The process of teaching and learningabout three-dimensional works of art with the sap of sana kebo and jarak gums as finishing material in class VI Kedungsari 5 Elementary School Magelang City and class VI SDLB-C Magelang City demonstrate the following facts: (1) the interaction between students with special needs students from regular classes are well established, this is characterized by smooth communication during the learning process and harmonious integration in several games, (2) there is no gap between students with special needs and students from regular classes in teaching and learning activities, (3) use the sap of sana kebo and jarak improve the quality of threedimensional artwork made from clay, (4) three-dimensional artwork that uses the sap of sana kebo and jarak have a more attractive appearance than without the sap of sana kebo and jarak, (5) the use of materials nature provided by the surrounding environment can be encouraged in the learning process, and (6) it is needed a more interesting learning package to increase students' imagination and creation. It can be concluded that the sap of sana kebo and jarak proved to be able to improve the quality of three-dimensional artworks of grade VI students of SD Negeri Kedungsari 5, Magelang City and grade VI SDLB-C.